Patterns of mental health service use among university students in Singapore - Tseng, Madeline Yu Qian (Nanyang Technological University, 2023)
Although mental health disorders are becoming more pervasive in Singapore, the usage of mental health services have been consistently low. Using Andersen’s Behavioural Model of Health Service Use, this study investigates the level of mental health utilisation among university undergraduates and identifies the predisposing, enabling and need factors associated with mental health service use in Singapore. 675 university undergraduates were surveyed online. Binary logistic regression was performed to explore the abilities of gender, social support, help-seeking attitudes, knowledge and fear of psychotherapy, belief about inability to find a psychotherapist, insurance and payment concerns and depressive symptoms severity in predicting the likelihood of mental health service use. Results revealed that students with higher levels of social support, less payment and insurance concerns, more negative help-seeking attitudes like a self-reliance mentality and less severe depressive symptoms were less likely to use mental health services. Gender, knowledge and fear of psychotherapy, belief about inability to find a psychotherapist, however did not significantly predict the likelihood of mental health service use. Depressive symptoms severity remained significantly associated with mental health service use, even after accounting for predisposing and enabling factors. Studying the dimensions that contribute to low mental health utilisation would inform the policy-making process in closing treatment gaps. Keywords: mental health service use, predisposing factor, enabling factor, need factor, Singapore